2021
DOI: 10.1021/acsomega.1c03132
|View full text |Cite
|
Sign up to set email alerts
|

Active Semisupervised Model for Improving the Identification of Anticancer Peptides

Abstract: Cancer is one of the most dangerous threats to human health. Accurate identification of anticancer peptides (ACPs) is valuable for the development and design of new anticancer agents. However, most machine-learning algorithms have limited ability to identify ACPs, and their accuracy is sensitive to the amount of label data. In this paper, we construct a new technology that combines active learning (AL) and label propagation (LP) algorithm to solve this problem, called (ACP-ALPM). First, we develop an efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Bayesian optimization focuses on finding the optimal value, while active learning is to reduce the amount of labeled data by selecting the most informative examples to label 27 . Current research has demonstrated that, when using the same annotation cost, exploring more informative regions through active learning can achieve higher performance than random exploration 28,29 . With the query strategy guided by the active learning algorithm, we can effectively evaluate the informativeness of each molecule and selectively explore the vast chemical space, reducing the huge annotation cost.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian optimization focuses on finding the optimal value, while active learning is to reduce the amount of labeled data by selecting the most informative examples to label 27 . Current research has demonstrated that, when using the same annotation cost, exploring more informative regions through active learning can achieve higher performance than random exploration 28,29 . With the query strategy guided by the active learning algorithm, we can effectively evaluate the informativeness of each molecule and selectively explore the vast chemical space, reducing the huge annotation cost.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning methods, such as convolutional neural networks (CNNs) and recurrent neural networks (RNNs), have been developed for the detection of 4mC sites, leveraging their ability to capture sequence patterns and dependencies, thereby contributing to accurate identification of these sites and enhancing our understanding of DNA methylation in gene regulation and epigenetics ( Xu et al, 2021 ; Liu et al, 2022 ). Yet there are still many deep learning methods that have not been applied, which have achieved great success in various application scenarios, including computer vision, speech recognition, biomarker identification ( Zeng et al, 2020 ; Cai et al, 2021 ) and drug discovery ( Chen et al, 2021 ; Zhang et al, 2021 ; Hu et al, 2022b ; Dong et al, 2022 ; Pan et al, 2022 ; Song et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%